Adaptive-passive control of structure-borne noise of rotating machinery using a pair of shunted inertial actuators. (July 2016) - Zhao, Guoying; Alujević, Neven; Depraetere, Bruno; Pinte, Gregory; Sas, Paul
In this article, two piezo-based rotating inertial actuators are considered for the suppression of the structure-borne noise radiated from rotating machinery. Each inertial actuator comprises a piezoelectric stack element shunted with the Antoniou's gyrator circuit. This type of electrical circuit can be used to emulate a variable inductance. By varying the shunt inductance it is possible to realise two tuneable vibration neutralisers to suppress tonal frequency vibrations of a slowly rotating machine. Also, reductions in the noise radiated from the machine housing can be achieved. First, a theoretical study is performed using a simplified lumped parameter model of the system at hand. The simplified model consists of a rotating shaft and two perpendicularly mounted shunted piezo-based rotating inertial actuators. Second, the shunted piezo-based rotating inertial actuators are tested on an experimental test bed comprising a rotating shaft mounted in a frame. The noise is radiated by a plate that is attached to the frame. The experimental results show that a reduction of 11 dB on the disturbance force transmitted from the rotating shaft through the bearing to the housing can be achieved. This also generates a reduction of 9 dB for the plate vibration and the radiated noise.